Submachine guns in the armed forces of the NATO countries - Kovačević, Nenad V.; Lazić, Goran M.; Đorđević, Igor Z. (Vojnotehnički glasnik / Military Technical Courier, 2019)
The paper presents a brief review of modern achievements and directions of further development of one type of small arms in the armament of foreign armed forces - namely, submachine guns in the armed forces of the countries signatories of the North Atlantic Treaty Organization (NATO). The article follows the historical genesis of the development of the use of submachine guns as specific types of small arms. Access to recent literature represented a major problem; consequently, data from the Internet was largely used. Submachine guns are one of the most effective and efficient types of infantry weapons of foreign armed forces so a more versatile look at the effects of their use is purposeful as well as the need for innovation and investing in our own resources. The article presents a synthesis of the authors’ practical experience with the use of submachine guns and the relevant theoretical knowledge.